Development of high-resolution melting curve analysis in rapid detection of vanA gene, Enterococcus faecalis, and Enterococcus faecium from clinical isolates - Sanaz Dehbashi; Hamed Tahmasebi; Parinaz Sedighi; Faeze Davarian; Mohammad Reza Arabestani (Tropical Medicine and Health, 2020)
Abstract Background High-resolution melting analysis (HRMA) is a novel molecular technique based on the real-time PCR that can be used to detect vancomycin resistance Enterococcus (VRE). The purpose of this study was to identify VRE species with HRMA in clinical isolates. Results Out of 49 Enterococcus isolates, 11 (22.44%) E. faecium isolates and 19 (38.77%) E. faecalis isolates were detected. Average melting temperatures for divIVA in E.faecalis, alanine racemase in E.faecium, and vanA in VRE strains were obtained as 79.9 ± 0.5 °C, 85.4 ± 0.5 °C, and 82.99 ± 0.5 °C, respectively. Furthermore, the data showed that the HRMA method was sensitive to detect 100 CFU/ml for the divIVA, alanine racemase, and vanA genes. Also, out of 49 Enterococcus spp., which were isolated by HRMA assay, 8 isolates (16.32%) of E. faecium and 18 isolates (36.73%) of E. faecalis were detected. The vanA gene was reported in 2 isolates (25%) of E. faecium and 9 isolates (50%) of E. faecalis. Conclusions This study demonstrated that using the HRMA method, we can detect E. faecium, E. faecalis, and the vanA gene with high sensitivity and specificity.